Enhancement of urea uptake in Chinese rice wine yeast strain N85 by the constitutive expression of DUR3 for ethyl carbamate elimination. Issue 2 (19th March 2015) - Li, Xiaomin; Shen, Chao; Wu, Dianhui; Lu, Jian; Chen, Jian; Xie, Guangfa
Abstract : Most of the fermented alcoholic beverages, particularly Chinese rice wine, contain the potentially human carcinogenic compound ethyl carbamate (EC). As a major EC precursor in Chinese rice wine, urea in fermentations can be transported into the yeast cell by urea permease and finally metabolized by urea carboxylase and allophanate hydrolase in vivo . To eliminate EC in Chinese rice wines, the present study constructed high urea uptake yeast strains N1‐D, N2‐D and N‐D, by introducing a strong promoter ( PGK1p ) into the urea permease gene ( DUR3 ) of the industrial Chinese rice wine yeast N85, and by the restoration of the URA3 gene at the same time. With these self‐cloned, high urea uptake strains, the urea and EC in the terminal Chinese rice wine samples were reduced to different extents. With two copies of overexpressed DUR3, the N‐D strain could reduce the urea and the EC by 53.4 and 26.1%, respectively. No difference in fermentation characteristics was found between the engineered strains and the parental industrial yeast strain N85. These results could help to optimize the genetic manipulation strategy for EC elimination in Chinese rice wine production. Copyright © 2015 The Institute of Brewing & Distilling